Cooperativismo e precarização do trabalho: um estudo aplicado na Cooperativa Recicla Conquista em Vitória da Conquista/BA - Santos, Adma Viana [UNESP] (2015)
In general, it appears that the actual extent / Concrete labor exploitation process, presents itself as a central phenomenon and quite complex in contemporary capitalist society, expressing itself through the activity of collectors of recyclable materials, for example, insofar as these turn out to be necessary for the reproduction process of capital, representing cheap and poor hand piece. They have organized themselves into cooperatives / associations, considering that these may mean in addition to income, a social place minor degradation; however, the cooperative has its contradictions. Through the above, the aim of this research was to understand the organization and territorial precarious work in the grooming of municipal solid waste and its structural condition for economic circuit of the recycling industry, based empirically on the Cooperativa Recicla Conquista, located in Vitoria da Conquista / BA. There was also the evidence of the professional career of collectors, their forms of resistance and collective organization materialized by this cooperative. Thus, in a broader perspective, this work aimed to contribute to the debate on the centrality of class work, the production of the economic circuit recycling, forms of organization and playback of workers collectors front of the capitalist system crisis and the role of the Government on the scavenging activity. For the development of the proposed objectives and following the theoretical orientation, empirical research was conducted with interviews and questionnaires to 54 cooperative...